Integration of Environmental Education in Waste Management through Ecobrick-Based Ecoliteracy Parks - Ika Niswatin Budiarti; Nurus Soimah; Dewi Qomariah Imelda; Nur Pujiati (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
This community service program aimed to raise public awareness of environmental conservation, strengthen literacy culture through open spaces, and encourage active community participation in creatively managing plastic waste. The method applied was Participatory Action Research (PAR), involving residents, the village government, Waste Treatment Facilities for Reduce, Reuse, and Recycle (TPS3R) managers, lecturers, and students from the planning to the implementation stages. The outcomes included establishing an Ecoliteracy Park with 1,500 ecobricks from household plastic waste, arranged into benches, a gazebo, a village landmark, educational boards, and garden borders. A total of 25 participants actively contributed to the construction and arrangement of the park, which was also enriched with ornamental plants and environmental-themed murals. The impacts observed were the enhancement of ecological awareness, the emergence of new waste sorting and recycling practices among residents, and the growing involvement of young people who utilize the park as a learning and interaction space. Beyond the physical facility, this program strengthened social cohesion, collective ownership of public spaces, and environmental responsibility. The Ecoliteracy Park thus serves as a sustainable educational medium and a replicable model of environmentally based community development with significant social impact